2013
DOI: 10.1007/s13277-013-0877-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a CLEIA automated assay system for the detection of a panel of tumor markers

Abstract: Tumor markers are commonly used to detect a relapse of disease in oncologic patients during follow-up. It is important to evaluate new assay systems for a better and more precise assessment, as a standardized method is currently lacking. The aim of this study was to assess the concordance between an automated chemiluminescent enzyme immunoassay system (LUMIPULSE® G1200) and our reference methods using seven tumor markers. Serum samples from 787 subjects representing a variety of diagnoses, including oncologic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…This might be due to the fact that these two immunoassay analyzers use a single monoclonal antibody for two-step sandwich immunoassay, while the other two assays use one or more different antibodies. Several comparative studies of CEA assays have been reported [ 12 15 18 19 20 ]. In one of these studies, CEA data obtained by Unicel DxI800 showed the highest degree of correlation with those measured by ADVIA Centaur XP [slope (95% CI), 0.910 (0.883 to 0.947); intercept (95% CI), −0.240 (−0.362 to −0.171)] [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that these two immunoassay analyzers use a single monoclonal antibody for two-step sandwich immunoassay, while the other two assays use one or more different antibodies. Several comparative studies of CEA assays have been reported [ 12 15 18 19 20 ]. In one of these studies, CEA data obtained by Unicel DxI800 showed the highest degree of correlation with those measured by ADVIA Centaur XP [slope (95% CI), 0.910 (0.883 to 0.947); intercept (95% CI), −0.240 (−0.362 to −0.171)] [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of PIVKA-II and AFP were measured by LUMIPULSE V R G1200 (Fujirebio-Europe, Belgium). [15] All assays were performed according to the manufacturers' instructions.…”
Section: Biomarker Assaysmentioning
confidence: 99%
“…Quantitative variations of serum tumor markers have been developed as non-invasive tools for the assessment of treatment efficiency in human malignancies [ 5 6 ]. In breast cancer, carcinoembryonic antigen (CEA), cancer antigen 125 (CA125) and cancer antigen 15-3 (CA15-3) are the most widely used serum tumor markers in clinical routine, although their usefulness remains controversial [ 5 , 7 ]. CEA is a glycoprotein, relevant for cell adhesion, and was the first tumor antigen that has been studied [ 8 ].…”
Section: Introductionmentioning
confidence: 99%